Etravirine combined with antiretrovirals other than darunavir/ritonavir for HIV-1-infected, treatment-experienced adults: Week 48 results of a phase IV trial. (18th January 2017) - Arathoon, Eduardo; Bhorat, Asad; Silaghi, Rodica; Crauwels, Herta; Lavreys, Ludo; Tambuyzer, Lotke; Van Baelen, Ben; Vanveggel, Simon; Opsomer, Magda
Objective: VIOLIN (TMC125IFD3002; NCT01422330) evaluated the safety, tolerability, and pharmacokinetics of etravirine with antiretrovirals other than darunavir/ritonavir in HIV-1-infected patients. Methods: In a 48-week, phase IV, single-arm, multicenter study, patients on prior antiretroviral therapy (⩾8 weeks) who needed to change regimen for virologic failure (viral load ⩾ 500 copies/mL) or simplification/adverse events (viral load < 50 copies/mL) received etravirine 200 mg bid with ⩾1 other active antiretroviral, excluding darunavir/ritonavir or only nucleoside/tide reverse transcriptase inhibitors. Results: Of 211 treated patients, 73% (n = 155) had baseline viral load ⩾ 50 copies/mL and 27% (n = 56) had baseline viral load < 50 copies/mL. Protease inhibitors were the most common background antiretrovirals (83%). Diarrhea was the most frequent adverse event (17%). Serious adverse events (no rash) occurred in 5% of patients; none were etravirine related. Overall, median etravirine AUC12h was 5390 ng h/mL and C0h was 353 ng/mL (N = 199). Week 48 virologic response rates (viral load < 50 copies/mL; Food and Drug Administration Snapshot algorithm) were 48% (74/155) (baseline viral load ⩾ 50 copies/mL) and 75% (42/56) (baseline viral load < 50 copies/mL). Virologic failure rates were 42% and 13%, respectively. The most frequently emerging etravirine resistance-associated mutations in virologic failures were Y181C, E138A, and M230L. Virologic response rates for patients with baseline viral load ⩾ 50 copies/mL were 38% (30/79) (non-adherent) versus 64% (44/69) (adherent subset). Conclusion: Etravirine 200 mg bid in combination with antiretrovirals other than darunavir/ritonavir was well tolerated in the studied treatment-experienced HIV-1-infected population. The overall etravirine safety and tolerability profile and pharmacokinetics (specifically in those patients who were adherent) were similar to those previously observed for etravirine in HIV-1-infected adults. The relatively high level of non-adherence, also observed in the pharmacokinetic assessments, negatively impacted virologic response, especially in patients with ⩾50 copies/mL at baseline.